Quinoxalinone (Part II). Discovery of (Z)-3-(2-(pyridin-4-yl)vinyl)quinoxalinone derivates as potent VEGFR-2 kinase inhibitors. Issue 8 (15th April 2016) - Shi, Leilei; Zhou, Jianfeng; Wu, Jifeng; Cao, Junya; Shen, Yuemao; Zhou, Hua; Li, Xun
Graphical abstract: Abstract: Inhibition of VEGFR-2 kinase has been highlighted as one of the well-defined strategies to suppress tumor growth via blockade of angiogenesis. Guided by the principles of bioisosteric replacement and pharmacophoric fragment migration, a series of novel quinoxalinone derivates were designed, synthesized and evaluated for their VEGFR-2 inhibitory potencies. Among them, compounds7c, 8b, 8c, 8e and10b displayed antiangiogenic abilities via the in vitro tube formation assay (cellular level) and ex vivo rat aortic ring assay (tissue level) at a low concentration (0.1 μM). By means of in vivo zebrafish embryo model, two ( Z )-3-(2-(pyridin-4-yl)vinyl)quinoxalinone derivates8c and8e showed significant antiangiogenesis effects, suggesting they have potentials to be developed into antiangiogenesis agents via further structural optimization. Moreover, these two compounds also demonstrated potent inhibition toward VEGFR-2 and B-raf kinases in a low concentration (1 μM). A possible interpretation of our evaluation result has been presented by a molecular docking study by docking representative compound8c with VEGFR-2.